Tidepools: using film-based ethnography to explore Black and Latino students' experience of community college. Issue 4 (8th August 2022) - Card, Polly
Abstract : This paper discusses Tidepools (Card 2017) a film-based ethnography produced to explore Black and Latino student experiences at community college. Tidepools (Card 2017) offers an innovative visual approach to data presentation and illuminates the importance of faculty and student relationships for Black and Latino successful academic experiences. Data were collected and analysed in two stages. Firstly, a short documentary film (N = 10) was produced using participant led visual methodology and a process-oriented analysis applied to understand student experiences at community college. Secondly, a discussion and pre- and post-survey (N = 50) were completed after screening Tidepools (Card 2017) at the National Consortium on College Men of Color Working Group, 2017 to assess the impact of the film on faculty members. Tidepools (Card 2017) reflects on and illuminates the importance of faculty and student relationships for Black and Latino student achievement at community college and has implications for the use of visual research and the professional development of faculty and policymakers to support Black and Latino students at community college.